2016
DOI: 10.1016/j.cbpa.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Salinity effects on plasma ion levels, cortisol, and osmolality in Chinook salmon following lethal sampling

Abstract: Studies on hydromineral balance in fishes frequently employ measurements of electrolytes following euthanasia. We tested the effects of fresh- or salt-water euthanasia baths of tricaine mesylate (MS-222) on plasma magnesium (Mg(2+)) and sodium (Na(+)) ions, cortisol and osmolality in fish exposed to saltwater challenges, and the ion and steroid hormone fluctuations over time following euthanasia in juvenile spring Chinook salmon (Oncorhynchus tshawytscha). Salinity of the euthanasia bath affected plasma Mg(2+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 56 publications
3
9
0
Order By: Relevance
“…Consistently, our studies showed significantly downregulated KEGG pathways associated with aldosterone-regulated salt and water balance (ko04960 and ko04978) (Figure 7E), indicating that ST trout show hydromineral dyshomeostasis. Previous studies in Chinook salmon (Oncorhynchus tshawytscha) showed the hydromineral balance is changed during euthanasia (111), which is consistent with our KEGG results. Based on this data, we propose positive feedback between severe infection and imminent death: (1) infection and its resulting stress response disturb the hydromineral homeostasis, thus resulting in a moribund condition.…”
Section: Glucocorticoid Receptor and Mineralocorticoid Receptorsupporting
confidence: 92%
“…Consistently, our studies showed significantly downregulated KEGG pathways associated with aldosterone-regulated salt and water balance (ko04960 and ko04978) (Figure 7E), indicating that ST trout show hydromineral dyshomeostasis. Previous studies in Chinook salmon (Oncorhynchus tshawytscha) showed the hydromineral balance is changed during euthanasia (111), which is consistent with our KEGG results. Based on this data, we propose positive feedback between severe infection and imminent death: (1) infection and its resulting stress response disturb the hydromineral homeostasis, thus resulting in a moribund condition.…”
Section: Glucocorticoid Receptor and Mineralocorticoid Receptorsupporting
confidence: 92%
“…The determination of the amounts of blood electrolytes, especially Na + , K + and Cl − , and osmolality and ion levels after changes in WS can provide information regarding the ionoregulatory ability and also successful acclimation of sh in a saline environment (Stewart et al, 2016). In the current research, the amounts of serum Na + and K + pronouncedly enhanced in sh reared at 35‰ that was associated with enhancing serum cortisol in this group indicating the increment tightening the junction between polygonal pavement cells in order to limit passive salt gain or loss during SW or FW acclimation, respectively (Chasiotis et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to fresh, brackish or salt water imposes a concentration gradient between the environment and the organism, and NKA activity plays an important role in maintaining homeostasis. Many recent data demonstrated that salinity has strongly increased NKA activity in many fish (Laverty & Skadhauge, 2012), such as spottedtail goby Synechogobius ommaturus (R.) (Shui et al., 2018), European sea bass Dicentrarchus labrax (Sinha et al., 2015) and Chinook salmon ( Oncorhynchus tshawytscha ; Stewart et al., 2016), while a few studies still suggested that the effects of salinity on branchial NKA activity were not significant (Kelly, Chow, & Woo, 1999; Yoshikawa, McCormick, Young, & Bern, 1993). Another more complex pattern of branchial NKA activity is that the lowest value is found in the salinity closed to their iso‐osmotic point (Shui et al., 2018; Urbina & Glover, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the HPS90 levels of fish in muscle for the 6 and 9‰ salinity treatments at 192 hr time point were the lowest points although they were not statistically different (p > .05; Figure 4b). goby Synechogobius ommaturus (R.) (Shui et al, 2018), European sea bass Dicentrarchus labrax (Sinha et al, 2015) and Chinook salmon (Oncorhynchus tshawytscha; Stewart et al, 2016), while a few studies still suggested that the effects of salinity on branchial NKA activity were not significant (Kelly, Chow, & Woo, 1999;Yoshikawa, McCormick, Young, & Bern, 1993). Another more complex pattern of branchial NKA activity is that the lowest value is found in the salinity closed to their iso-osmotic point (Shui et al, 2018;Urbina & Glover, 2015).…”
Section: Hsp90 Content In Liver and Musclementioning
confidence: 99%